2014
DOI: 10.4028/www.scientific.net/amr.941-944.780
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Superplasticizer S-3 on the Technological Properties of Concrete Mixtures

Abstract: In the process designing of concrete arise the problem - compatibility polycarboxylates with cement different parties. In some cases, when you receive the next batch of cement concrete mobility decreased sharply. Additive had to pick again. When choosing supplements examined its effect on the technological properties of concrete mixtures: workability, resistance to water gain, air entrainment. Test results showed that the addition of superplasticizer based on sulfonated naphthalene-formaldehyde resins (SNF) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…Modifier proportion (in % of the weight) is: silica fume in a composition of SicaFume (20%), fine ash-and-slag composite from the Uglegorskaya Thermal Power Plant (30%), fluidifier [14] (2%) and fly ash from the Zuyevskaya Thermal Power Plant (48%).…”
Section: Specimens With Steel Fiber Reinforcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Modifier proportion (in % of the weight) is: silica fume in a composition of SicaFume (20%), fine ash-and-slag composite from the Uglegorskaya Thermal Power Plant (30%), fluidifier [14] (2%) and fly ash from the Zuyevskaya Thermal Power Plant (48%).…”
Section: Specimens With Steel Fiber Reinforcementmentioning
confidence: 99%
“…High-strength concrete with organic-mineral modifier 10-01 MB [13] in the amount of 20% of cement weight containing silica fume, fly ash, fluidifier [14] and concrete hardening controller has been used in the tests. Concrete mix components: 490 kg/m 3 of Portland cement 42.5 (M500); 549 kg/m 3 of silica sand with the fineness modulus of 1.9; 1100 kg/m 3 of crushed granite fractions 5...20 mm; 153 l/m 3 of water.…”
Section: Specimens With Confinement Reinforcementmentioning
confidence: 99%
“…Barabanshchinok and M.V. Komarinsky found that some additives are not combined with certain types of cements: they do not show required properties [10]. In this regard, it is necessary to select the type of an additive depending on the type of cement.…”
Section: S Izotov and Rmentioning
confidence: 99%
“…Lesovik, S.A.Yu. Murtazaev [16][17][18][19][20][21][22][23][24][25], the use of «inert» dispersed MF in concrete mixtures not only does not reduce the strength of the filled cement binder, but also in some cases even leads to its hardening.…”
Section: Introductionmentioning
confidence: 99%